The influence of digital leadership and work environment on employee performance at BPKPD of Tebing Tinggi City - Rizky Eggy Chandra Bu’ulolo; Hasrudy Tanjung (Economic: Journal Economic and Business, 2026)
Digital transformation in the public sector requires technology-adaptive leadership and a supportive work environment to enhance employee performance. This study examines the partial and simultaneous effects of Digital Leadership and the Work Environment on Employee Performance at the Regional Financial and Revenue Management Agency (BPKPD) of Tebing Tinggi City. A quantitative approach with an explanatory survey design was employed. The study population consisted of 92 employees, with 88 respondents included in the statistical analysis. Data were collected using a five-point Likert-scale questionnaire and analyzed through multiple linear regression using IBM SPSS Statistics. The results show that Digital Leadership has a positive and significant effect on Employee Performance (beta = 0.391, t = 4.452, p less than 0.001), while the Work Environment also has a positive and significant effect (beta = 0.456, t = 5.200, p less than 0.001). Simultaneously, both variables significantly affect Employee Performance (F(2,85) = 56.313, p less than 0.001), with an Adjusted R² of 0.560. These findings highlight the importance of strengthening digital leadership capabilities and maintaining supportive workplace conditions to improve employee performance in public-sector organizations undergoing digital transformation.